Severe Microcytic Anaemia and Acute Respiratory Distress Syndrome in a Rheumatoid Arthritis Patient on Long-Term Corticosteroids: A Case Report - Palivela, Nandini; Landa, Suchitra (Indian Journal of Pharmacy Practice, 2026)
Rheumatoid Arthritis (RA) is a chronic autoimmune disorder associated with multiple extra-articular manifestations, including hematological abnormalities and pulmonary complications. Anaemia in RA is often multifactorial, and prolonged corticosteroid therapy further increases the risk of infections and systemic complications. A 38-year-old female with a one-year history of rheumatoid arthritis on long-term deflazacort therapy presented with generalized weakness, fatigue, and progressive dyspnoea. Laboratory investigations revealed severe microcytic hypochromic anaemia with a haemoglobin level of 3.6 g/dL and low reticulocyte count. During hospitalization, the patient developed worsening respiratory symptoms and was diagnosed with bilateral lower lobe pneumonia progressing to Acute Respiratory Distress Syndrome (ARDS). Management included packed red blood cell transfusion, broad-spectrum antibiotics, oxygen therapy, and supportive care, resulting in gradual clinical improvement with haemoglobin rising to 8.9 g/dL. This case highlights the complex interplay among chronic inflammation, severe anaemia, and corticosteroid-induced immunosuppression in patients with rheumatoid arthritis. Early identification of anaemia and prompt management of infections are essential to prevent life-threatening complications such as ARDS. Multidisciplinary care plays a crucial role in improving clinical outcomes.
Keywords: Acute Respiratory Distress Syndrome; Corticosteroid Treatment; Extra-articular; Manifestations; Microcytic Anaemia; Pulmonary Infection; Rheumatoid Arthritis